ANALYSIS OF THE COMPOSITION OF DIRECT SPENDING AND INDIRECT SPENDING AT THE ENVIRONMENTAL SERVICES IN ENREKANG REGENCY - Syarifuddin Yusuf; Nurwani M; Devi Milayanti (Journal AK-99, 2022)
This study aims to determine the composition of direct and indirect spendingat the Environmental Services in Enrekang Regency. The data collection techniques used in this study was interviews and documentation. The sample in this study were the statement of budget realization from Regional Revenues and Expenditure Budget (RREB) for the Environmental Servicesin Enrekang Regency from 2017 to 2019 period. The data analysis technique used in this study was expenditure compatibility analysis. The results of the study showed that: 1) In 2017-2019 periode, it can be seen that the allocation of direct spending and indirect spending of the Environment Services in Enrekang Regency was 62,76% : 37,24% in 2017; 70,78% in 2018: 29,22% and in 2019 it was 69,88%: 30.12%. Thus, in 2017 the composition of regional spending was not ideal; 2) In 2018 and 2019 the composition of regional spending was ideal, which means that in those years the Environmental Service in Enrekang Regency had used their regional spending for regional economic development; 3) The procedure for direct spending and indirect spending at the Environmental Service in Enrekang Regency is accordance with domestic regulations Number 21 of 2011 aboutGuidelines for Regional Financial Management.